Financial Literacy, Financial Management, Social Legitimacy and Being FOMO on Impulsive Buying: Evidence on Leisure Activity Coldplay Concert Euphoria on Indonesian Gen Z Generation - Mukti, Aloysius Harry; Sastrodiharjo, Istianingsih; Hariyanto, Oda I.B (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
The primary objective of this research is to examine the effects of financial literacy, financial management, social legitimacy, and the Fear of Missing Out (FOMO) on the impulsive buying behaviors of Indonesian Generation Z in the context of attending high-profile concerts, specifically Coldplay's concert. This study addresses the scarcity of research on the influence of big concert events on financial behavior and impulsive buying tendencies among the Indonesian Gen Z generations, highlighting the need for comprehensive financial management and literacy in the face of social pressures and FOMO. The research utilized an online survey conducted between January 1st and February 28th, 2023, targeting Indonesian Gen Z individuals. The sample consisted of 356 respondents, with data analysis performed using the Partial Least Squares (PLS) technique to assess the relationships between financial literacy, financial management, social legitimacy, FOMO, and impulsive buying behavior. The findings reveal that FOMO and social legitimacy positively contribute to impulsive buying behavior, while financial literacy negatively impacts such behaviors. Surprisingly, better financial management was also associated with higher impulsive buying, indicating a complex interplay between financial preparedness and the allure of social events. The study's limitations include its reliance on self-reported data through an online questionnaire and the potential lack of representativeness of the wider Indonesian Gen Z population. The methodology might not fully capture the long-term impacts of financial literacy and management on impulsive buying behavior. This research introduces a novel perspective by integrating the concept of big concert events as a significant factor influencing the financial behaviors of young Indonesians. It bridges a crucial research gap by elucidating the role of social legitimacy and FOMO alongside financial literacy and management in shaping impulsive buying tendencies, offering insights into the targeted financial education strategies to mitigate such behaviors.